Numerical Analysis of Ground Motion Topographic and Geological Effect: A Case Study of MOXI Platform - Zhao, Shixing; Luo, Qirui; Tang, Yuanxu; Xia, Jing; Li, Yingmin; Zhang, Min (Civil Engineering Journal, 2025)
The ground motion amplification effect influenced by diverse topographic and geological conditions was investigated to enhance the seismic design standards for mountain structures. A comprehensive series of two-dimensional and three-dimensional numerical simulations was conducted. These simulations utilized idealized and real-world topographic models, meticulously considering various critical parameters, such as platform height, width, slope, surface angle, and soil properties. The results reveal that topographic and geological factors both significantly impact the ground motion amplification effect, with the maximum amplification factors frequently surpassing those stipulated by the current Chinese seismic code. Based on these findings, a refined and modified formula was developed for calculating the ground motion amplification factor that integrates the influences of height, width, slope, and geological conditions. The validity and feasibility of this modified formula were substantiated thoroughly through detailed comparisons between the actual observed values and the suggested values, demonstrating its potential to improve the safety and reliability of seismic design in mountainous regions substantially.